Situs Inversus Totalis: An incidental finding in a fatal case of road traffic accident - Kumar, Vivek; Kumar , Gautam; Prasad, Rajib; Kumar Deb , Prabir; Maitra, Rumi; Kumari , Madhuri (Journal of Indian Academy of Forensic Medicine, 2020)
Human body is externally symmetrical but internally asymmetrical due to genetic makeup. The genetic mutation to the genes responsible for the reversal of handed asymmetry causes the condition called situs inversus. The incidence of situs inversus is 1 in 10000 to 1 in 50000 birth.1 Situs inversus is most of the time an incidental finding during investigation for some other problem, otherwise, they live a normal healthy life. In some cases, few complications are seen frequently with situs inversus eg: congenital heart disease (like ASD, VSD etc), Kartagener syndrome, infertility etc. Situs inversus sometimes produces difficulties in making diagnosis. Situs inversus also open negligence cases against doctors due to misdiagnosis of some disease conditions like acute appendicitis, cholecystitis etc. or non-information of cases of situs inversus during taking consent of any procedure or surgery. We encountered a case of situs inversus totalis as an incidental finding during postmortem examination in NBMC Darjeeling.